Comparison of immunogenicity between intradermal and intramuscular injections of repeated annual identical influenza virus strains post-pandemic (2011-2012) in COPD patients - Benjamas Chuaychoo; Uraiwan Kositanont; Parichat Niyomthong; Nuttapol Rittayamai; Sorachai Srisuma; Kanokwan Rattanasaengloet; Walaiporn Wongsrisakunkaew; Julalux Thongam; Thaweesak Songserm (Human Vaccines & Immunotherapeutics, 2020)
We compared the antibody responses and persistence of the reduced-dose, 9 µg hemagglutinin (HA)/strain intradermal (ID) injection via the Mantoux technique and the 15 μg HA/strain intramuscular (IM) injection of the repeated annual identical trivalent, inactivated, split-virion vaccine 2011–2012 in chronic obstructive pulmonary disease (COPD) patients. Eighty patients were randomized to ID (n = 41) and IM (n = 39) groups. Four weeks post-vaccination, the antibody responses of the two groups were similar; those for influenza A(H1N1)pdm09 and influenza A(H3N2)–but not influenza B–met the criteria of the Committee for Proprietary Medicinal Products (CPMP). The antibody responses for influenza A(H1N1)pdm09 rapidly declined in both groups, especially with the ID injection, whereas those for influenza A(H3N2) maintained above the CPMP criteria throughout 12 months post-vaccination. The geometric mean titres for influenza A(H1N1)pdm09 persisted above the protective threshold (≥ 40) until 6 months post-vaccination in both the ID and IM groups. The seroprotection rates of the ID and IM groups were above 60% until 3 months and 6 months post-vaccination, respectively. In conclusion, the 9 μg HA/strain ID injection of vaccine 2011–2012 elicited antibody responses similar to the standard dose of 15 μg of the HA/strain IM injection at 4 weeks post-vaccination. However, the antibody responses for influenza A(H1N1)pdm09 rapidly declined, especially in the case of the ID injection, whereas they were comparable for influenza A(H3N2). Additional strategies for increasing vaccine durability should be considered, especially for new pandemic strains affecting elderly COPD patients.